Early Childhood Sex Education to Prevent Sexual Abuse - Farantika, Dessy; Purwaningrum, Devia; Nindiya, Devi Candra; Prawinda, Raras Ayu; Sofwan, Arif Muzayin; Sanjaya, Maulinda Sulistiyani (Jurnal Pendidikan Anak Usia Dini, 2024)
Cases of sexual harassment are currently receiving serious attention because they often occur in various environments, including play areas, schools and families. This research aims to investigate the role of parents and teachers, as well as the strategies, methods and materials taught in the learning process at Al Muhajirin Kindergarten, Malang City. The type of research carried out was qualitative research with descriptive methods. Data collection was carried out through interviews and observations. The results of this study illustrate that sex education from an early age has a significant role. Educational institutions and the role of parents have a big influence on children's understanding of sex education.